2014
DOI: 10.1155/2014/748531
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Free Radical Scavenging Activity of a Wild Edible Mushroom, Sparassis crispa (Wulf.) Fr., from North Western Himalayas, India

Abstract: Bioactive compounds and antioxidant activity of methanolic extract ofSparassis crispacollected from North Western Himalayan region of India were analyzed. Phenolic content11.14±0.08 mg tannic acid equivalent per g of the extract and flavonoids1.96±04 mg catechin equivalent per g of the extract were recorded to be the major antioxidant components in this wild edible mushroom. Significant antioxidant efficiency on inhibition of 2,2-diphenyl-1-picrylhydrazyl (DPPH) was observed when compared to standard antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…were found to be potent antioxidants in the concentration range of 40-60 μ g/mL and 10-70 μ g/mL, respectively. However, a previous study reported that the radical scavenging activity of mushroom extracts was shown at 2.11 mg/mL [26]. The possible reasons for the varied results of antioxidant activities between the present and previous study might be due to the different extraction conditions, and the difference in the presence of phenolic compounds and other secondary metabolites [2729].…”
Section: Discussionmentioning
confidence: 53%
“…were found to be potent antioxidants in the concentration range of 40-60 μ g/mL and 10-70 μ g/mL, respectively. However, a previous study reported that the radical scavenging activity of mushroom extracts was shown at 2.11 mg/mL [26]. The possible reasons for the varied results of antioxidant activities between the present and previous study might be due to the different extraction conditions, and the difference in the presence of phenolic compounds and other secondary metabolites [2729].…”
Section: Discussionmentioning
confidence: 53%
“…All of the mushroom extracts in the current investigation had significant FRS activities in doses ranging from 10 g/mL to 70 g/mL. On the other hand, a prior investigation found that the FRS activity of mushroom extracts was 2.11 mg/mL [ 39 ]. The existence of numerous different secondary metabolites and differences in the quantity and potency of phenolic compounds are likely to be the primary causes of the inconsistent results of the free radical scavenging activities between the current report and earlier ones [ 40 42 ].…”
Section: Discussionmentioning
confidence: 75%
“…In particular, β-glucan can prevent and heal common health problems such as diabetes, cancer, wound healing, as well as immune system and cytokine induction [ 1 , 6 , 12 , 13 , 14 , 15 ]. In addition, phenolic compounds, anti-fungal substances, and other S. crispa extracts may be used as anti-oxidant or anti-fungal agents [ 3 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%